Ambidextrous leadership, creative self-efficacy, self-resilience, trust in supervisor and employee innovative performance in the telecom industry of Pakistan - Inam Ullah Khan; Shrafat Ali Sair; Rizwan Qaisar Danish; Muhammad Adnan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
This study analyses how ICT leaders/ managers / supervisors' ambidextrous leadership associates with the innovative performance of employees through trust in the supervisor, self-resilience, and creative self-efficacy. Data was collected in total from 450 employees ranging from the first line workers i.e., 350, while 100 managers / supervisors within the time span of 2 weeks. The SPSS and AMOS v23 software were used for the data analysis of survey results. This study used ambidexterity theory for leadership and for employees' perspective used to broaden and build theory. This study hypothesized that there is a relationship between ambidextrous leadership, self-resilience, and trust in supervisor that affects the innovative performance of employees, such that ambidextrous leadership has the strongest positive relationship with innovative performance when employees have high levels of self-resilience and trust in supervisor. Moreover, creative self-efficacy mediates the relationship between the ambidextrous leadership and employee innovative performance. Results indicate that there is a positive effect of ambidextrous leadership on employee innovative performance when the self-resilient of employees are high and they trust their managers or supervisors at work place.
Keywords: 330; ambidextrous leadership; creative self-efficacy; innovative performance; selfresilience; trust in supervisor; telecom industry